Morphology and anatomy of leaf miners in two species of Commelinaceae (Commelina diffusa Burm. f. and Floscopa glabrata (Kunth) Hassk) - Elb,Paula Maria (2010)
In specialized literature, reports on anatomy of miners in host plants are few in number. These agents trigger excavations, or paths, by consumption of plant inner tissues by larvae of several insects. The aim of this work was to investigate leaf miner occurrence in Commelina diffusa (a cosmopolitan plant) and Floscopa glabrata (an amphibious plant) using anatomical techniques. The place where the plants were collected is subjected to seasonal floods, consequently both the species were exposed to the same weather conditions and seasonal floods. This study showed that members of Agromyzidae and Chironomidae families, which are Diptera endophytophagous larvae types, were responsible for the tunnels. Moreover, in Commelina diffusa Agromyzidae larvae were found, while in Floscopa glabrata three Chironomidae cephalic exuviae were found. The miners, as can be seen from anatomical studies, used only mesophyll parenchyma tissues for feeding, causing the formation of linear mines. In addition, in both the species, the epidermis and the medium-sized vascular units were kept intact, showing no structural modification, such as neoformation of tissues.